Legal and Traditional Construction in Wedding Ceremonies: A Sociological Legal Perspective - Muslim, Dendi Ramdani; Rizkia, Nabila Subur; Ahmad, Beni (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the construction of formal law and customary traditions in marriage ceremonies should mutually support and accommodate the cultural values of the community. Formal law is expected to provide universal legal certainty, while customary traditions function as social regulators that reflect local identities and values. However, in reality, there is often a misalignment between these two legal systems, which can lead to conflicts and tensions, especially when customary law contradicts national legal provisions. This misalignment presents a significant challenge in creating harmony between formal law and customary traditions, particularly in the context of customary marriages. The purpose of this research is to examine the interaction between the construction of formal law and customary traditions in marriage ceremonies and to identify the challenges that arise from the fundamental differences between the two. The research concludes that despite the gap between formal law and customary traditions, efforts to bridge the two through cultural dialogue and the recognition of customary law can create an inclusive and just legal system. An integrative approach is needed that involves indigenous communities in the legislative process to ensure that the law applied is not only legally relevant but also socially and culturally appropriate.